Serum Fibroblast Growth Factor 21 Levels Are Positively Associated with Metabolic Syndrome in Patients with Type 2 Diabetes - Ruo-Yao Gao; Bang-Gee Hsu; Du-An Wu; Jia-Sian Hou; Ming-Chun Chen (International Journal of Endocrinology)
Background. Fibroblast growth factor 21 (FGF21) acts as a potent metabolic regulator. Serum FGF21 levels were significantly higher in obesity and type 2 diabetes mellitus (T2DM) populations. The aim of this study was to evaluate the relationship between serum FGF21 levels and metabolic syndrome (MetS) in T2DM patients. Methods. Fasting blood samples were obtained from 126 T2DM patients. MetS and its components were defined according to the diagnostic criteria from the International Diabetes Federation. Serum FGF21 concentrations were measured using a commercially available enzyme-linked immunosorbent assay. Results. Among these patients, 84 (66.7%) had MetS. Female gender, hypertension, systolic blood pressure (SBP), diastolic blood pressure (DBP), waist circumference (WC), body weight (BW), body mass index (BMI), body fat mass, fasting glucose, glycated hemoglobin level (HbA1c), triglyceride level (TG), urine albumin-to-creatinine ratio (UACR), insulin level, homeostasis model assessment of insulin resistance (HOMA-IR), and FGF21 levels were higher, whereas high-density lipoprotein cholesterol level (HDL-C) and estimated glomerular filtration rate (eGFR) were lower in DM patients with MetS. Univariate linear analysis revealed that hypertension, BMI, WC, body fat mass, SBP, DBP, logarithmically transformed TG (log-TG), low-density lipoprotein cholesterol (LDL-C) level, log-glucose, log-creatinine, log-UACR, log-insulin, and log-HOMA-IR positively correlated, whereas HDL-C and eGFR negatively correlated with serum FGF21 levels in T2DM patients. Multivariate forward stepwise linear regression analysis revealed that body fat mass (adjusted R2 change = 0.218; P=0.008) and log-TG (adjusted R2 change = 0.036; P<0.001) positively correlated, whereas eGFR (adjusted R2 change = 0.033; P=0.013) negatively correlated with serum FGF21 levels in T2DM patients. Conclusions. This study showed that higher serum FGF21 levels were positively associated with MetS in T2DM patients and significantly positively related to body fat mass and TG but negatively related to eGFR in these subjects.